2010
DOI: 10.1016/j.pec.2009.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and success of nurse telephone counseling in linguistically isolated Korean American patients with high blood pressure

Abstract: Objective Nurse telephone counseling can improve the management of chronic conditions, but the effectiveness of this approach in underserved populations is unclear. This study evaluated the use of bilingual nurse-delivered telephone counseling in Korean Americans (KAs) participating in a community-based intervention trial to improve management of hypertension. Methods KAs were randomized to receive 12 months of hypertension-related telephone counseling that was more intensive (bi-weekly) or less intensive (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 26 publications
(30 reference statements)
0
54
1
2
Order By: Relevance
“…Cultural adaptations and individual tailoring, or subgroup analysis of outcomes of interest was not reported for the Asian American subgroups in these three large RCT studies. Following these study exclusions, seven studies were identified for review (Sun et al, 1996, Liao et al, 2002, Han et al, 2010, Qi et al, 2011, Dirige et al, 2013, Islam et al, 2013, Wang et al, 2013). Table 1 provides a descriptive summary of reviewed studies including: RTC design characteristics, sample characteristics, intervention characteristics, cultural appropriateness assessment, risk of bias assessment, and evidence of efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cultural adaptations and individual tailoring, or subgroup analysis of outcomes of interest was not reported for the Asian American subgroups in these three large RCT studies. Following these study exclusions, seven studies were identified for review (Sun et al, 1996, Liao et al, 2002, Han et al, 2010, Qi et al, 2011, Dirige et al, 2013, Islam et al, 2013, Wang et al, 2013). Table 1 provides a descriptive summary of reviewed studies including: RTC design characteristics, sample characteristics, intervention characteristics, cultural appropriateness assessment, risk of bias assessment, and evidence of efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Three out of seven RCTs identified a theoretical framework to guide the intervention design. Two (Han et al, 2010, Qi et al., 2011) used Bandura's social cognitive learning and self-efficacy theory (Bandura, 1989), and one (Dirige et al, 2013) used the transtheoretical model (Prochaska and DiClemente, 1983). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…전 화상담은 시간과 의료비용의 절감 등의 이점을 가지고 있 으며 (Kolt, Schofield, Kerse, Garrett, & Oliver, 2007;Reese, Conoly, & Brossart, 2006), 실증적 연구를 통해서도 당뇨 환자의 경우, 당 및 지질대사, 자가간호, 자기효능감의 증진에 효과적이고 (Kim, Cho, & Nam, 2008;Kim & Chung, 2002;Long, Gambling, Young, Taylor, & Mason, 2005;Lorig, Ritter, Villa, & Piette, 2008;Song & Kim, 2007), 고 혈압 환자의 혈압관리와 자가간호행위의 증가 (Han et al, 2010), 치매 환자 가족의 자기효능감과 자기간호의 증 가 (Lee, Kim, Kim, & Shin, 2004), 노인의 신체활동 증가 (Kolt et al, 2007), 성인의 식이변화 효과 (Newman, Flatt, & Pierce, 2008 …”
unclassified